Análisis sociológico de la desigualdad social en la novela cholos de Jorge Icaza - Macas Armijos, Valeria Daniela (2015)
The present research is named “ANÁLISIS SOCIÓLOGICO DE LA DESIGUALDAD SOCIAL EN LA NOVELA CHOLOS DE JORGE ICAZA”; focuses on the story of social inequality. It was developed through a literary analysis causing a general objective of analyzing the principal features of social inequality in the work of Jorge Icaza “Cholos”. To this end certain methods were applied: scientific, inductive-deductive, analytic-synthetic and the specific method for the literary analysis was the narrational. From this research will conclude that there are economical and social features such as the lack of education, clothing, arrengements, the whitening, poverty, injustice, submisiveness of the rights, and the enforcement of the public services due to the hierarchy of classes. This is why we recommend the study of the realistic ecuadorian novels in order to know the social and economic realities of a century ago which still prevail in the current society.